Comparative Genomics Analysis of Plasmid pPV989-94 from a Clinical Isolate of Pantoea vagans PV989 - Lei Xu; Min Yin; Tingyuan Zhu; Yabo Liu; Yuanyuan Ying; Junwan Lu; Chaoqing Lin; Jianchao Ying; Teng Xu; Liyan Ni; Qiyu Bao; Shunfei Lu (International Journal of Genomics)
Pantoea vagans, a gram-negative bacterium from the genus Pantoea and family Enterobacteriaceae, is present in various natural environments and considered to be plant endophytes. We isolated the Pantoea vagans PV989 strain from the clinic and sequenced its whole genome. Besides a chromosome DNA molecule, it also harboured three large plasmids. A comparative genomics analysis was performed for the smallest plasmid, pPV989-94. It can be divided into four regions, including three conservative regions related to replication (R1), transfer conjugation (R2), and transfer leading (R3), and one variable region (R4). Further analysis showed that pPV989-94 is most similar to plasmids LA637P2 and pEA68 of Erwinia amylovora strains isolated from fruit trees. These three plasmids share three conservative regions (R1, R2, and R3). Interestingly, a fragment (R4′) in R4, mediated by phage integrase and phage integrase family site-specific recombinase and encoding 9 genes related to glycometabolism, resistance, and DNA repair, was unique in pPV989-94. Homologues of R4′ were found in other plasmids or chromosomes, suggesting that horizontal gene transfer (HGT) occurred among different bacteria of various species or genera. The acquired functional genes may play important roles in the adaptation of bacteria to different hosts or environmental conditions.